2022
DOI: 10.3390/ma15062120
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Vapour Deposition of Scandia-Stabilised Zirconia Layers on Tubular Substrates at Low Temperatures

Abstract: The paper presents results of investigation on synthesis of non-porous ZrO2-Sc2O2 layers on tubular substrates by MOCVD (metalorganic chemical vapor deposition) method using Sc(tmhd)3 (Tris(2,2,6,6-tetramethyl-3,5-heptanedionato)scandium(III), 99%) and Zr(tmhd)4 (Tetrakis(2,2,6,6-tetramethyl-3,5-heptanedionato)zirconium)(IV), 99.9+%) as basic reactants. The molar content of Sc(tmhd)3 in the gas mixture was as follows: 14, 28%. The synthesis temperature was in the range of 600–700 °C. The value of extended Grx/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…They reported that higher pressures resulted in lower gas flow and a thicker diffusion layer. Recently, Sawka [319] also synthesised ScSZ layers on tubular substrates using the MOCVD route in the temperature range of 600-700 • C using Zr(tmhd) 4 and Sc(tmhd) 3 by optimising the synthesis conditions including Grashof number (Gr), Reynolds number (Re), and distance from the gas flow input (x). The results showed a low value of about 0.01 for the extended Gr x /Re x 2 .…”
Section: Chemical Vapour Deposition (Cvd) Processmentioning
confidence: 99%
“…They reported that higher pressures resulted in lower gas flow and a thicker diffusion layer. Recently, Sawka [319] also synthesised ScSZ layers on tubular substrates using the MOCVD route in the temperature range of 600-700 • C using Zr(tmhd) 4 and Sc(tmhd) 3 by optimising the synthesis conditions including Grashof number (Gr), Reynolds number (Re), and distance from the gas flow input (x). The results showed a low value of about 0.01 for the extended Gr x /Re x 2 .…”
Section: Chemical Vapour Deposition (Cvd) Processmentioning
confidence: 99%
“…A considerable number of research articles report ZrO 2 structures obtained by different methods, such as the following: sol-gel method [18], magnetron sputtering [19,20], chemical vapor deposition [21], electron beam physical vapor deposition (EBPVD) [22], laser ablation [23], hydrothermal method [24], and atomic layer deposition [25]. A key element in the design of zirconia nanostructures is the choice of technique and approach for their elaboration, which ensures the presence of needed properties and qualities, and predetermines specific applications.…”
Section: Introductionmentioning
confidence: 99%